PERENCANAAN SISTEM DRAINASE KAWASAN KAMPUS UNIVERSITAS MADAKO TOLITOLI - Melda (LPPM Universitas Madako Tolitoli, 2026)
In the Madako Tolitoli University campus area, waterlogging often occurs because there is no drainage infrastructure. Puddles that occur can cause damage to the main campus road construction and disrupt the learning process, so it is necessary to arrange a drainage system in the Madako Tolitoli University campus environment. The purpose of this study is to design a drainage system in the Madako Tolitoli University campus area, to plan the dimensions of the drainage channel that can accommodate water discharge according to its capacity. The method used is the rational method. The data needed are area data, rainfall data, for the calculation of rainfall intensity is the value of rainfall distribution log person III 5 year return period, for rainfall intensity using the mononobe formula. Based on the data analysis, it is planned that 26 rectangular channels are planned with details of 1 main channel, 15 carrier channels and 10 collector channels, and the amount of rainwater produced by the channel is 1,076 m3/s and the drainage channel discharge capacity is 1,166 m3/s.